Comparison of the lipid content and fatty acid composition of two hulled oats and their hull with naked and dehulled oats varieties - Kshitiz Pokhrel; Lenka Kouřimská; Novel Kishor Bhujel; Rasmita Parajuli; Matěj Božik (Czech Journal of Food Sciences)
Oat (Avena sativa Linnaeus) has distinctive multifunctional characteristics and nutritional profile, as well as a large amount of oat-processing by-product comprises hulls, which contain lipids and other nutrients. In this study, the lipid content and fatty acid (FA) profiles of six naked oat varieties (Kamil, Marco Polo, Oliver, Patrik, Santini, and Saul), two hulled oat varieties (Atego and Korok), and their dehulled grains and hulls were analysed. The findings of the study demonstrated that the lipid content varied from 4.14 g.100 g-1 dry matter (DM) (Santini) to 6.68 g.100 g-1 DM (Kamil) in naked oats; 3.61 g.100 g-1 DM in Atego and 3.47 g.100 g-1 DM in Korok with hull; 0.70 g.100 g-1 DM in Atego hull and 0.71 g.100 g-1 DM in Korok hull. Dehulled oats had a higher lipid content than hulled oats. Linoleic and oleic acids were the predominant FAs in analysed samples. Oat hulls contained maximum amounts of saturated FAs (SFAs) (26% in Korok and 25.6% in Atego). Elimination of hulls raised the amount of linoleic acid and decreased the amount of oleic acid. Oat hull contained the least amount of linoleic acid and the highest amount of C20:0 (eicosanoic acid) and C22:0 (docosanoic acid). Oats are a significant source of lipids, predominantly comprising unsaturated fatty acids (UFAs). Moreover, oat hulls contribute to the lipid content although their FA composition, with higher palmitic acid and lower linoleic acid levels, differs from that of naked, hulled, and dehulled oats.